Shepherds of the southern Andean highlands: religiosity, territory and ecological balance - Merlino, Rodolfo J. (1983)
In this paper we present an interpretive synthesis of data on the religiosity of shepherds, obtained in an area of ​​the Southern Andean Altiplano, which is located in the NW of the Argentine province of Jujuy, near the borders with Chile and Bolivia. These data were collected in three field works, carried out in different periods of the years 1977, 1978 and 1979. The main scenario was the house of a family of shepherds settled about 20 km. south of Mina Pirquitas, using said house, which simultaneously served us as a shelter, as a base for our operations. We also work in other positions of the same family, as well as with neighboring families.